The Effects of Advertising Strategies on Consumer Trust: A Case of Skin Care Products in Taiwan - Velly Anatasia; Sunitarya Sunitarya; Vinda Adriana (Bina Nusantara University, 2016)
The main aim of this study was to develop advertising strategies in order to increase consumer trust. Four advertising elements: celebrity endorsement, branding, product attribute, and third party certification were investigated. Data were collected to answer two research questions: (1) To investigate the advertising strategies of skin care products leading to consumer trust, (2) To know the effects of advertising strategies in skin care products on consumer trust. A 5-point Likert scale survey was distributed to the female population in Taipei area. Via online and personal approaches, 266 questionnaires were returned. Targeting on 18-30 years old female skin care product users who stay in Taipei area more than six months, 240 qualified questionnaires were analyzed. The four independent variables are found having a significant relationship with trust in skin care advertising, in which branding has the greatest influence on increasing consumer trust. The control variable which is financial status is not found having statistically significant effect on consumer trust. To conclude, this study is dedicated to the communities in order to optimize their marketing strategies.